AN ANALYSIS OF THE ABILITY OF THIRD YEAR STUDENTS OF SMPN 04 DAYUN IN WRITING DESCRIPTIVE TEXTS - Wati, Sudiana; Hadriana, Hadriana; Gultom, Effendy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This is a descriptive research which is aimed at findings out the levels writing ability of the third year students of SMPN 04 Dayun. 22 students of IX.1 were chosen as the sample of this research is obtained by using cluster random sampling technique. The instrument of the test is in the form of writing test. The students’ writing ability scores are measured by three raters. After being measured, the data are analyzed by the writer. Based on the research findings, the students’ ability in writing descriptive texts can be categorized at good level because the total mean score is 62.88. The students’ ability in terms of grammar was in mediocre level (60.9). The students’ ability in terms of content was in good level (62.1). The students’ ability in terms of mechanics was in good level (63.9). The students’ ability in terms of vocabulary was in good level (64.5). The students’ ability in terms of organization was in good level (63.0). From 5 aspects as indicators, the highest mean score was in vocabulary (64.5), because the students have the kinds of word for the writing test, and the lowest mean score was in grammar (60.9), because the students still have problem that tenses, singular plural and adjective. In conclusion, the students have good ability in writing descriptive texts.Key words: Analysis, Writing Ability, Descriptive Texts